Fuzzy logic control (FLC)-based coordination control of DC microgrid with energy storage system and hybrid distributed generation. Issue 1 (31st December 2022) - Bharathi, G.; Kantharao, P.; Srinivasarao, R.
ABSTRACT: The developed and developing countries are going to install a number of distributed generations (DGs) with lucrative incentives. In recent years, DC microgrids have got remarkable popularity throughout the world due to dc output sources, namely, batteries, solar panels, and fuel cells are interconnected without the presence of ac/dc conversion. In this paper, the photovoltaic (PV) system is proposed with the fuel cell (FC) and battery bank in the micro-gird system at various dynamic conditions. Besides, fuzzy logic controller is suggested to regulate the bus voltage and retain the power balance. In order to ascertain the effectiveness of the suggested control approaches, the system has been verified with various dynamic conditions like 50% changes in AC and DC loads, irradiance variations, overloading situations and the battery bank functioning when the change in FC is observed. The simulation outcomes disclose that the fuzzy-based proposed method renders better dynamic performances with proposed energy storage systems.